On adhesion mechanism of salivary pellicle‐PDMS interface. Issue 3 (3rd September 2019) - Ma, Genlei; Tang, Yue; Zeng, Qihang; Zheng, Jing
Abstract : The adsorption behaviour of salivary proteins on polydimethylsiloxane (PDMS) surface was investigated here, aiming to fully understand the interfacial adhesion mechanism. Human whole saliva was derived from a healthy donor. Adsorption kinetics of salivary proteins on PDMS surface was examined by quartz crystal microbalance with dissipation (QCM‐D). The morphology and shear energy of the salivary pellicle were characterised using nano‐scratch technique, and its adhesion force was measured by means of atomic force microscopy. Results show that a rough but dense viscoelastic pellicle with a high binding strength is formed on the PDMS surface through the adsorption of salivary proteins. Saliva adsorption obviously increases the PDMS surface wettability but has no influence on its zeta potential. The adhesion force of the pellicle is near zero initially, but it increases significantly with the time. In summary, no electrostatic interaction occurs at the salivary pellicle‐PDMS interface. The bonding of salivary pellicle to PDMS surface is mainly resulted from hydrophobic interaction and is time‐dependent.